The rationale for state custodianship of mineral resources under the MPRDA: a conceptual analysis of equitable access to the mining industry and black economic empowerment - Mpiko, Xabiso Gift (Department of Private Law, 2025)
The dissertation investigates the rationale behind the state custodianship of mineral resources in South Africa, as enshrined in the Mineral and Petroleum Resources Development Act (MPRDA) 28 of 2002. This legislative framework marked a significant shift from private to state control over the country's mineral wealth, aiming to correct historical injustices rooted in colonial and apartheid policies. Central to the MPRDA is the pursuit of equitable access to the mining industry and the advancement of Black Economic Empowerment (BEE), which are considered crucial components of the broader socio-economic transformation agenda. The research provides a theoretical analysis of how the custodianship model functions within the context of South Africa's Constitution, particularly section 25, which mandates the state to use its resources for public interest and social justice. The state's role as custodian is evaluated through its legislative and regulatory actions, focusing on how it facilitates access to mining opportunities for historically disadvantaged groups. Key aspects of the analysis include the interaction between the MPRDA, the Broad-Based Black Economic Empowerment Act (BBBEEA) 53 of 2003, and the Mining Charter of 2018, which aim to promote economic inclusivity in the mining sector. The study critically assesses whether these policies have successfully transformed the ownership structures of mining enterprises and promoted meaningful black participation in the industry. It highlights the various challenges that persist, including bureaucratic inefficiencies, financial barriers, and fronting practices, which undermine the goals of black economic empowerment. Methodologically, the dissertation employs a desktop and doctrinal legal research approach. The desktop method involves collecting information from secondary sources such as textbooks, academic journals, dissertations, government statistics, whitepapers, and newspapers. Meanwhile, the doctrinal legal research method utilises primary legal sources such as case law, legislation, and policy documents. The study identifies both the successes and shortcomings of the state custodianship model, particularly the role of the Minister of Mineral Resources in granting mining rights and ensuring that these rights align with the objectives of equitable access and transformation as espoused in the MPRDA. The dissertation concludes that while progress has been made in transforming the mining industry under state custodianship, significant gaps remain. These include insufficient support for emerging black mining businesses, the limited success of ownership transfers, and the inconsistent application of the Mining Charter due to its nature as policy and not law. The research advocates for more robust regulatory oversight, better financial mechanisms, and more proactive state involvement to ensure that the transformation goals of the MPRDA are fully realised.